The Effect of Self-Control and Work Environment on Cyberloafing Behavior among Employees of PT Buana Sawit Indah - Suci Haryanti Manurung; Fitri Hayati; Faisal Umardani Hasibuan (International Journal Of Economics Social And Technology, 2026)
This study aims to examine the influence of self-control and work environment on cyberloafing behavior among employees of PT Buana Sawit Indah. A quantitative approach with a causal research design was employed, involving 52 employees as respondents. Data were collected through a structured questionnaire and analyzed using multiple linear regression analysis. The findings indicate that both self-control and work environment have a significant negative effect on cyberloafing behavior, both individually and simultaneously. Employees with higher levels of self-control tend to demonstrate greater discipline in regulating their online activities and are less likely to engage in non-work-related internet use during working hours. Similarly, a supportive work environment characterized by clear organizational policies, effective supervision, and a positive organizational climate contributes to reducing employees' tendency to engage in cyberloafing behavior. These findings suggest that cyberloafing behavior is influenced not only by individual factors but also by organizational conditions. Therefore, efforts to minimize cyberloafing should focus on enhancing employees’ self-regulation capabilities while simultaneously fostering a conducive work environment. Organizations are encouraged to implement policies that strengthen behavioral control, establish clear guidelines regarding internet usage, and create a positive workplace atmosphere to improve employee productivity and organizational performance.